Reliability-based optimized design of hybrid tether - Agrawal A.K.; Pratap M.; Sati S.C.; Upadhyay R.K. (My University, 2025)
Purpose: The purpose of this paper is to optimize the design of a hybrid tether using probabilistic approach considering inherent random variation in the stress developed and the strength it has. The variation in strength is mostly because of variation in diameter of the tether and the properties of the material along the length of the tether. As a result, classical design approach for the tether may not serve the purpose. For this purpose, a reliability-based design of hybrid tether is discussed in this paper. Design/methodology/approach: A literature review was carried out on the design of tether and its operational reliability. It has been shown that the classical design approach does not serve the purpose, as the strategic operation has to be reliable enough, often requiring a measure of reliability required. A reliability-based approach has been presented to achieve the optimum design of a hybrid tether. Findings: The optimization problem was carried out for different values of the safety factor to investigate the effect on the optimal design of tether. An analysis is carried out to show that one should not target a very high value of reliability or factor of safety, as it causes the self-weight of the tether to increase tremendously and its cost significantly. Research limitations/implications: The present work has been carried out considering the limited data and can further be extended to determine more accurate reliability measures by considering more number of sample test data. The measured data is collected from limited required trials for demo; do not represent the exact population data. Originality/value: Lab strength test and flight trials were conducted to acquire data for the present analysis. In field use, it was noticed that the tether degraded from top portion attached toward the balloon end because of maximum exposure and repeated usage. © 2020, Emerald Publishing Limited.